Buttocks Hard as Rocks: Not Wanted after Aortic Dissection Repair - Cameron-Gagné, Maude; Bédard, Luc; Lafrenière-Bessi, Valérie; Lévesque, Marie-Hélène; Dagenais, François; Langevin, Stéphan; Laflamme, Maxime; Voisine, Pierre; Jacques, Frédéric (AORTA, 2018)
The authors report the case of a patient developing a gluteal compartment syndrome after DeBakey type I dissection repair. Prompt recognition and treatment led to successful results. The surgical approach to the gluteal compartment is described.
Keywords: gluteal compartment syndrome; type A aortic dissection repair; aortic dissection complication